CAR-NK cell therapy: promise and challenges in solid tumors - Balkhi, Sahar; Zuccolotto, Gaia; Di Spirito, Anna; Rosato, Antonio; Mortara, Lorenzo (Frontiers in Immunology, 2025)
Over the past few years, cellular immunotherapy has emerged as a promising treatment for certain hematologic cancers, with various CAR-T therapies now widely used in clinical settings. However, challenges related to the production of autologous cell products and the management of CAR-T cell toxicity highlight the need for new cell therapy options that are universal, safe, and effective. Natural killer (NK) cells, which are part of the innate immune system, offer unique advantages, including the potential for off-the-shelf therapy. A recent first-in-human trial of CD19-CAR-NK infusion in patients with relapsed/refractory lymphoid malignancies demonstrated safety and promising clinical activity. Building on these positive clinical outcomes, current research focuses on enhancing CAR-NK cell potency by increasing their in vivo persistence and addressing functional exhaustion. There is also growing interest in applying the successes seen in hematologic malignancies to solid tumors. This review discusses current trends and emerging concepts in the engineering of next-generation CAR- NK therapies. It will cover the process of constructing CAR-NK cells, potential targets for their manufacturing, and their role in various solid tumors. Additionally, it will examine the mechanisms of action and the research status of CAR-NK therapies in the treatment of solid tumors, along with their advantages, limitations, and future challenges. The insights provided may guide future investigations aimed at optimizing CAR-NK therapy for a broader range of malignancies.